The Analysis of Recirculation Zone and Ignition Position of Non-Premixed Bluff-Body for Biogas Mild Combustion - M. M., Noor; Wandel, Andrew P.; Talal, Yusaf (Universiti Malaysia Pahang, 2013)

(untitled)
Combustion ignition study is important due to the combustion process becoming more lean and efficient. This paper studied the recirculation zone and ignition location for the bluff-body non-premixed MILD burner with biogas used as fuel. The location of the ignition was critical to ensure the spark energy supply during the ignition process is successful ignite the mixture of air and fuel. The numerical calculations were done using the commercial code ANSYS-Fluent to simulate the furnace with bluff-body burner to determine the recirculation zone. The turbulence model used was the realizable k-ε model. The inner recirculation zone between the air and fuel nozzle is the best location for the ignition point since low velocity of air and fuel mixing will assist the ignition process. This is because the ignition energy will have time to ignite the mixture in the low speed of turbulent swirl flow. The most suitable location with the highest possibility of ignition is the centre of the recirculation zone.